Valor forrajero de trece especies de Stipa de Mendoza - Wainstein, Pedro (1962)
Thirteen species of Stipa proceeding from the Mendoza province, are studied from the point of view of bromatology and foraging; the results show that the quality of these grasses is superior before their flowering, in what concerns the part eaten by the cattle (the upper two thirds of the plants) The best specimens studied can be compared with oat hay, cut during its full flowering, the nutritive relation being in one of the studied samples 1 to 6.83, and in other, 1 to 6.85. It has been demonstrated that the forage value of these grasses decreases as their vegetative condition advance.